Contemporary issues in social science - Grima, Simon; Özen, Ercan; Boz, Hakan (Emerald Publishing Limited, 2021)
This special edition of Contemporary Studies in Economic and Financial Analysis offers twenty-three chapters by invited participants in the International Applied Social Science Congress. In these chapters chronical a wide variety of important issues such as: Volatility spillover between conventional stock index and participation index; The Interplay Between Experience, Satisfaction and Positive Word of Mouth: A Study on City Marketing in Afyonkarahisar and more. This international and wide-ranging exploration on different economic systems provides a comprehensive account which brings a wide range of countries to the forefront in terms of both comparability and accountability, this study shines a light on the differences in systems between states, and provides timely and accurate information to equip readers to minimize those differences.
Includes index.
Keywords: Economics.; Business & Economics -- Economic Conditions.; Economic history.; elektronické knihy; electronic books